1993
DOI: 10.1128/aem.59.11.3602-3604.1993
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Nitrogen Utilization in Acremonium coenophialum Isolates

Abstract: Acremonium coenophialum, a fungal endosymbiont in tall fescue, is responsible for the production of alkaloid toxins. Animals grazing endophyte-infected tall fescue often show toxicosis. In marginal environments, the endophyte is important for long-term survival of tall fescue. Few differences in endophyte isolates from individual tall fescue plants have been reported. To aid development of a toxicosis-free tall fescue, it is important to identify differences in endophyte isolates. This report describes variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Kulkarni and Nielsen (1986) showed that a N. coenophialum strain could assimilate NH + 4 but not NO − 3 as a source of N from the growth medium. In contrast, three out of four N. coenophialum isolates from Kentucky‐31 tall fescue analyzed by Ferguson et al (1993) could utilize NO − 3 and all of them could utilize NH + 4 as N source. Naffaa et al (1998b) examined growth of endophytes from 12 grass species of Poaceae and found that all of them (including N. lolii ) could assimilate NH + 4 but only A. chilense ‐like endophytes (a‐endophytes) could assimilate NO − 3 These results suggest a considerable variability in N utilization among endophyte isolates from different grass species.…”
Section: Adaptations and Mechanisms Of Mineral Stress Tolerancementioning
confidence: 89%
“…Kulkarni and Nielsen (1986) showed that a N. coenophialum strain could assimilate NH + 4 but not NO − 3 as a source of N from the growth medium. In contrast, three out of four N. coenophialum isolates from Kentucky‐31 tall fescue analyzed by Ferguson et al (1993) could utilize NO − 3 and all of them could utilize NH + 4 as N source. Naffaa et al (1998b) examined growth of endophytes from 12 grass species of Poaceae and found that all of them (including N. lolii ) could assimilate NH + 4 but only A. chilense ‐like endophytes (a‐endophytes) could assimilate NO − 3 These results suggest a considerable variability in N utilization among endophyte isolates from different grass species.…”
Section: Adaptations and Mechanisms Of Mineral Stress Tolerancementioning
confidence: 89%
“…Lactose and casein are the optimal carbon and nitrogen sources for E. festucae (Li et al, 2008). Ferguson et al found that the best nitrogen sources for the mycelial growth of E. coenophiala are proline and potassium nitrate (Ferguson et al, 1993). The growth of E. festucae is significantly improved by cellulase, tryptone, casein peptone, proline, and peptone (Ma, 2009).…”
Section: Introductionmentioning
confidence: 99%